Team effectiveness: epidemiologists' perception of collective performance during emergency response - Amy Elizabeth Parry; Alice Richardson; Martyn D. Kirk; Samantha M. Colquhoun; David N. Durrheim; Tambri Housen (BMC, 2023)
Abstract Background To describe epidemiologists' experience of team dynamics and leadership during emergency response, and explore the utility of the Team Emergency Assessment Measure (TEAM) tool during future public health emergency responses. The TEAM tool included categories for leadership, teamwork, and task management. Methods We conducted a cross-sectional survey between October 2019 and February 2020 with the global applied field epidemiology workforce. To validate the TEAM tool for our context, we used exploratory and confirmatory factor analysis. Results We analysed 166 completed surveys. Respondents included national and international emergency responders with representation of all WHO regions. We were unable to validate the TEAM tool for use with epidemiology teams involved in emergency response, however descriptive analysis provided insight into epidemiology emergency response team performance. We found female responders were less satisfied with response leadership than male counterparts, and national responders were more satisfied across all survey categories compared to international responders. Conclusion Functional teams are a core attribute of effective public health emergency response. Our findings have shown a need for a greater focus on team performance. We recommend development of a fit-for-purpose performance management tool for teams responding to public health emergencies. The importance of building and supporting the development of the national workforce is another important finding of this study.